Design and realization of an open‐source and modular smart meter. Issue 4 (6th June 2019) - Sayed, Sawsan; Hussain, Tasnim; Gastli, Adel; Benammar, Mohieddine
Abstract: This paper presents the design of a modular and open‐source smart meter for educational and research purposes. The smart meter monitors the energy consumption, uploads the data to a cloud server, and can be used to control appliances remotely through a control relay. Using the Internet of Things (IoT) technology, the smart meter acts as a sensing node in a meshed network. This enables consumers to visualize their energy consumption profiles at the level of appliances and to take control actions to manage efficient energy consumption using the automation platforms or IoT with smart meters. In this paper, the energy consumed by different electrical appliances is computed and communicated to a server using the Arduino Uno board aided by the ESP8266 WiFi module. The energy consumption is also displayed on an LCD screen, and the consumption profiles are displayed through the home energy monitoring website "EmonCMS." The design can accommodate different transducer ratings with single‐phase and three‐phase measurements by configuring itself automatically using the plug‐and‐play approach. The realization of the proposed smart meter is a multicourse educational project that aims to polish students' skills in applying the knowledge gained in Electrical Engineering (ie, undergraduate courses) to produce a practical application. Abstract : This paper presents a design of an open‐source and modular smart meter for teaching and research purposes that can be easily adapted to different applications and environments.